Social representations, emotions, and behaviors toward marine animals: An exploratory study - Godinho, S.; Garrido, M. V. (Anthrozoös, 2025)
Orcas, also known as killer whales, have been ramming sailing boats near Spain, Portugal, and Morocco, concerning the sea community and feeding hate speech. Yet, little is known about how humans perceive wild marine animals as social groups. Acknowledging the relevance of the two fundamental dimensions of social cognition – warmth (benign or ill intent) and competence (high or low ability) – we used the Stereotype Content Model (SCM) and the Behaviors from Intergroup Affect and Stereotypes map to identify stereotypes, emotions, and behavioral tendencies associated with marine animals. To explore the social representation of these animals, we conducted three studies (nTotal = 761) asking a heterogeneous sample currently living in 24 different countries to rate 24 wild marine animals on warmth and competence (Study 1), report their emotions and behavioral intentions (Study 2), and report their conservation attitudes toward each animal species (Study 3). Results showed that marine animals could be represented on the four clusters advanced in the SCM, replicating stereotypic profiles like those found for human groups. Warmth and competence judgments also predicted particular emotional and behavioral tendencies along with conservation attitudes toward marine animals. Unveiling how this profiling on the bi-dimensional space relates to emotional and behavioral tendencies toward each group could inform the design of biodiversity protection-related policies as well as tailored awareness and conservation campaigns.